Spatial localization of knowledge-transfer channels and face-to-face contacts: A survey of the Jena university-industry linkages - Thomas Sauer; Matthias-Wolfgang Stoetzer; Andrea Gerlach (Ernst-Abbe-Fachhochschule Jena, Fachbereich Betriebswirtschaft, 2007)
In this paper we examine the knowledge-Transfer Channels of the universities and public research institutes in Jena. The empirical study is based on a survey of 297 personal interviews with researchers of both types of organisations. Our study focuses on three questions: (a) The importance and multitude of existing transfer channels, (b) their geographic distribution and (c) the importance of face-to-face contacts. With regard to the first question the analysis reveals some shortcomings of the usual channels considered in many empirical studies. Above all, informal transfer channels play an important role and in addition the multitude of transfer channels at hand turns out to be large. These outcomes suggest a very cautious interpretation of the claimed influences of transfer mechanisms like patents, joint publications and so on. As to the regional distribution of the linkages our results confirm the relevance of geographical proximity. A substantial part of the relevant transfer co-operations concentrate on the city and region. Finally, we examine the idea that 'distance matters' is due to the necessity of face-to-face contacts. By means of asking the researchers directly we found the puzzling result, that knowledge-transfer rests significantly upon personal contacts, but that this does not imply a bias towards geographical proximity.
urn:nbn:de:gbv:27-20100929-163249-5
Keywords: O31; O32; R12; 330